Răspuns :
Răspuns:
Explicație pas cu pas:
a)
(4 + 4 + 5) : 3 = 13 : 3 = 4,(3)
b)
(4 + 4 + 6) : 3 = 14 : 3 = 4,(6)
c)
(4 + 4 + 7) : 3 = 15 : 3 = 5
d)
(4 + 4 + 8) : 3 = 16 : 3 = 5,(3)
e)
(4 + 4 + 9) : 3 = 17 : 3 = 5,(6)
f)
(4 + 4 + 10) : 3 = 18 : 3 = 6
Salutare!:)
[tex]m.a = \frac{4 + 4 + 5}{3} = \frac{13}{3} = \boxed{4.(3)} \\ \\ m.a = \frac{4 + 4 + 6}{3} = \frac{14}{3} = \boxed{4.(6)} \\ \\ m.a = \frac{4 + 4 + 7}{3} = \frac{15}{3} = \boxed{5} \\ \\ m.a = \frac{4 + 4 + 8}{3} = \frac{16}{3} = \boxed{5.(3)} \\ \\ m.a = \frac{4 + 4 + 9}{3} = \frac{17}{3} = \boxed{5.(6)} \\ \\ m.a = \frac{4 + 4 + 10}{3} = \frac{18}{3} = \boxed{6} [/tex]